Growth, Yield, and Nutrient Content of Habanero Chili (Capsicum chinense) in Response to Different Pineapple Leaf Biochar and Trichoderma Biofertilizer Ratios - Suraiya Mahdian; Hasmah Mohidin; Khadijah Khalid; Rosazlin Abdullah; Nurmaliena Rosli; Syahira Jos (AGRIVITA Journal of Agricultural Science)
Culturing Capsicum chinense using a fertigation system necessitates a significant amount of chemical fertilizer, leading to diminishing nutrient levels in both the crop and the growing medium over time. This study investigates an alternative method: recycling pineapple leaves into biochar and combining it with Trichoderma biofertilizer (TBF) to enhance crop growth, yield, and nutrient content. Conducted in a randomized complete block design (RCBD) under rain shelter conditions, seven treatments are tested: T0 (Commercial chemical fertilizer - Control), T1 (Commercial organic fertilizer), T2 (100% pineapple leaf biochar [PLB]), T3 (100% TBF), T4 (75% PLB + 25% TBF), T5 (50% PLB + 50% TBF), and T6 (25% PLB + 75% TBF). The parameters measured include growth, yield, and nutrient content of the total plant biomass after destructive sampling. The treatment with 75% PLB and 25% TBF yielded results comparable to the control, significantly enhancing plant height (68.24 cm), stem diameter (1.12 cm), SPAD chlorophyll content (53.83), yield (403.69 g), total plant biomass (156.13 g), and nutrient content. While the control (T0) shows the highest values for some growth parameters, T4 emerges as the most promising ratio, offering significantly higher mean values for both growth and yield parameters among the organic treatments studied.